OSTEOPOROSIS AND SOME RELATED FACTORS IN ELDERLY PEOPLE GOING TO HOSPITAL AT NINH BINH PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2021)
Objective: 1. To survey the status of osteoporosis in elderly people who come to the general hospital of Ninh Binh province for medical examination; 2. To analysis of some factors related to osteoporosis. Methods: A cross-sectional descriptive study was conducted on 385 elderly patients who visited the examination department of the Ninh Binh Provincial General Hospital from July 2020 to September 2021. Result: More than half of the study subjects had lumbar spine osteoporosis (59.5%), the rate of lumbar spine bone loss was 30.4%. The rate of lumbar spine osteoporosis is 18.7% and the rate of femoral neck bone loss is 45.5%. The prevalence of osteoporosis is markedly higher in women than in men, and in people over 70 years old than in younger people. Risk factors for osteoporosis in study subjects included body mass index, having 5 or more risk factors, and having 3 or more chronic diseases. Risk factors for osteoporosis in women include age at menopause, duration of menopause, number of births, duration of breastfeeding, and oophorectomy status. Smoking and alcohol consumption are considered risk factors for osteoporosis in men. Conclusion: The prevalence of osteoporosis is quite high in the elderly and is related to age, gender, some reproductive health factors in women and risk behaviors in men.
Keywords: Osteoporosis, elderly people, bone density.